2016
DOI: 10.1186/s13068-016-0648-1
|View full text |Cite
|
Sign up to set email alerts
|

Dry-grind processing using amylase corn and superior yeast to reduce the exogenous enzyme requirements in bioethanol production

Abstract: BackgroundConventional corn dry-grind ethanol production process requires exogenous alpha and glucoamylases enzymes to breakdown starch into glucose, which is fermented to ethanol by yeast. This study evaluates the potential use of new genetically engineered corn and yeast, which can eliminate or minimize the use of these external enzymes, improve the economics and process efficiencies, and simplify the process. An approach of in situ ethanol removal during fermentation was also investigated for its potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…the full integration of pretreatment, hydrolysis and fermentation towards ethanol in a single microbial process step, remains a ‘holy grail’ in lignocellulosic ethanol production. Engineered starch-hydrolysing S. cerevisiae strains are already applied in first-generation processes (Kumar and Singh 2016 ). The first important steps towards efficient cellulose and xylan hydrolysis by S. cerevisiae have been made by functional expression of heterologous polysaccharide hydrolases (Olson et al.…”
Section: Discussionmentioning
confidence: 99%
“…the full integration of pretreatment, hydrolysis and fermentation towards ethanol in a single microbial process step, remains a ‘holy grail’ in lignocellulosic ethanol production. Engineered starch-hydrolysing S. cerevisiae strains are already applied in first-generation processes (Kumar and Singh 2016 ). The first important steps towards efficient cellulose and xylan hydrolysis by S. cerevisiae have been made by functional expression of heterologous polysaccharide hydrolases (Olson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical yields were estimated based on the starch content, assuming complete starch conversion and 100% fermentation efficiency. Actual ethanol yields were determined by calculating liquid volume in final slurry at end of fermentation (Kumar and Singh 2016 ). Final slurry was weighed and a sample of the slurry was dried in hot air oven at 105 °C till constant weight was achieved (~24 h) to estimate the solid percent in the slurry.…”
Section: Methodsmentioning
confidence: 99%
“…The results suggested that damaged starch content had more impact on the starch hydrolysis and ethanol production than did the particle size of dry-grind corn. A regular dent corn was reported to provide 2.9 gal/bu ethanol yield via a conventional dry-grind corn process (Lemuz et al 2009;Kumar and Singh 2016). Therefore, sample A provided comparable ethanol yield (2.93-2.98 gal/bu) to the regular dent corn, whereas sample D gave higher ethanol yield (3.00-3.02 gal/bu) than the regular one.…”
Section: Resultsmentioning
confidence: 99%
“…Mill types used for dry-grinding affected the ethanol production for all samples, especially after 24 and 48 h fermentation time. A regular dent corn was reported to provide 2.9 gal/bu ethanol yield via a conventional dry-grind corn process (Lemuz et al 2009;Kumar and Singh 2016). All hammer-milled samples showed the lowest ethanol production at 72 and 96 h. The differences in ethanol yield between the cyclone-and hammer-milled samples ranged from 0.1 to 0.4% at 72 h. After 96 h, the ethanol yield differences between the cyclone-and hammermilled samples ranged from 0.0 to 0.2%.…”
Section: Resultsmentioning
confidence: 99%